New Classification Schemata of Hypersensitivity Adverse Effects After Hyaluronic Acid Injections: Pathophysiology, Treatment Algorithm, and Prevention. Issue 11 (November 2020) - Mikkilineni, Radha; Wipf, Angela; Farah, Ronda; Sadick, Neil
Abstract : BACKGROUND: Side effects during hyaluronic acid (HA) injection are considered mild and reversible; however, an alarming trend of increased hypersensitivity reactions has recently been reported. OBJECTIVE: The goal of this article is to review the hypersensitivity reactions reported in the literature and, in combination with the authors' experience, to create a classification system to sort the timing and clinical manifestations of these reactions, as well as a treatment schema to manage their clinical course. METHODS: A literature search using PubMed, Ovid MEDLINE, and Embase databases was performed with no date restrictions. Search terms included "hyaluronic acid and hypersensitivity" and "hyaluronic acid and nodules." Data analyzed included study type, number of subjects, HA filler type, injection location, adverse reaction, timing, treatment, and outcomes. RESULTS: Thirty-six studies were identified, documenting hypersensitivity reactions to HA treatment. Twelve cases described events occurring within a week, 6 within a month, and 31 after a month of treatment. Combined with the authors' experience, a new classification system and management of hypersensitivity reactions to HA fillers is proposed of early (up to a week), intermediate (a week to a month), and late (over a month) hypersensitivity reactions. CONCLUSION: The classification system proposed provides objective measurements and management options that can be helpful for physicians to navigate these hypersensitivity reactions and design treatment protocols that provide the best clinical outcomes for their patients.